Using the MEROPS Database for Proteolytic Enzymes and Their Inhibitors and Substrates. Issue 1 (12th December 2014) - Rawlings, Neil D.; Barrett, Alan J.; Bateman, Alex
Abstract: MEROPS is a database of proteolytic enzymes as well as their inhibitors and substrates. Proteolytic enzymes and protein inhibitors are organized into protein domain families. In turn, families are organized into clans. Each peptidase, inhibitor, family, and clan has associated annotation, a multiple sequence alignment, a phylogenetic tree, literature references, and links to other databases. Interactions between proteolytic enzymes and inhibitors and between proteolytic enzymes and substrates are also presented. The entries in MEROPS are available via the World Wide Web. This unit contains detailed information on how to access and utilize the information present in the MEROPS database. Details on running MEROPS both remotely and locally are presented. © 2014 by John Wiley & Sons, Inc.